Recovery of mixed volatile fatty acids from anaerobically fermented organic wastes by vapor permeation membrane contactors - TUĞTAŞ KARNABAT, ADİLE EVREN; YEŞİL, HATİCE (ELSEVIER SCI LTD, 2018)
Volatile fatty acids (VFAs) are attractive compounds in renewable based bio-refinery industries and can be produced through anaerobic digestion of organic wastes. Nevertheless, the recovery of VFAs from anaerobically digested organic wastes is the bottleneck of the resource recovery. In this study, VFA recovery from synthetic VFA solutions and fermented organic wastes via air-filled and tertiary amine extractant-filled PTFE membranes through vapor pressure membrane contactors (VPMC) was investigated. Acetic acid was recovered with greater than 45% efficiency in all the fermented wastes. Recovery of propionic, butyric, valeric, and caproic acids through trioctylamine-filled PTFE membrane was greater than 86% and 95% from landfill leachate and fermentation broth of anaerobically digested organic waste, respectively. This study reveals that VFA separation can be effectively achieved via economic and environmental friendly VPMC system and the process is implementable as it can be coupled to a fermentation process to prevent inhibition and to recover VFAs.
Keywords: Acidogenic fermentation; Carboxylate platform; Membrane; Organic waste; Separation and recovery; VFAs; CARBOXYLIC-ACIDS; PERVAPORATION MEMBRANES; AQUEOUS-SOLUTIONS; LIQUID-MEMBRANE; GAS MEMBRANES; SOLID-WASTES; ACETIC-ACID; EXTRACTION; REMOVAL; WATER